2020
DOI: 10.52547/jvesselcirc.1.4.45
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Johnson’s Behavioral System Model in a Patient With Heart Failure: A Case Study

Abstract: Background and Aim: Patients with heart failure encounter numerous problems. The current study aimed to explore the effects of Johnson's behavioral system model (JBSM) on the care of patients with heart failure, considering all aspects of their behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…These results are in agreement with those of Ghanbari Afra and Mohammad Hoseini who conducted a case study evaluating the effect of Johnson's behavioral system model on the care of a patient with heart failure in a hospital a liated to Qom University of Medical Sciences. They showed that after using Johnson's model, the patient's unstable behaviors were reduced in terms of the aggressive-protective subsystem [19]. Johnson's behavioral system model emphasizes the evaluation of, and intervention with, the individual's behavioral system in a non-invasive manner.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with those of Ghanbari Afra and Mohammad Hoseini who conducted a case study evaluating the effect of Johnson's behavioral system model on the care of a patient with heart failure in a hospital a liated to Qom University of Medical Sciences. They showed that after using Johnson's model, the patient's unstable behaviors were reduced in terms of the aggressive-protective subsystem [19]. Johnson's behavioral system model emphasizes the evaluation of, and intervention with, the individual's behavioral system in a non-invasive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Some Iranian Master's nursing students have also examined the effects of applying a nursing theory on patients in their thesis. Therefore, several papers have been published on the effectiveness of the nursing theories presented by Orem, 19 Roy, 20,21 Watson, 22 and some other theorists 23,24 in different groups of patients. In Iran, however, no course on nursing theories is offered in the bachelor's degree program in nursing.…”
Section: Introductionmentioning
confidence: 99%